Projeção dos impactos socioeconômicos do programa de transferência de renda em Brumadinho e região - Milenna Diniz Cordeiro (2024)
The disaster that occurred on January 25, 2019, with the rupture of the tailings dam at the Córrego do Feijão Mine, owned by Vale S.A., in Brumadinho, Minas Gerais, is considered the largest human and environmental disaster in Brazil, causing immense human, economic, social, and environmental losses. This event triggered the need for measures of repair and recovery in the affected areas, including the implementation of an Income Transfer Program (ITP). The ITP, along with other actions, was a response adopted to mitigate the economic impacts in the regions affected by the disaster. The judicial agreement for reparation, ratified in February 2021, involved the payment of R$4.4 billion by Vale S.A., aimed at repairing the affected population. This emergency aid is considered the largest private income transfer program in the world. The dissertation aims to investigate the economic impacts of the ITP on the benefited municipalities, with an emphasis on regional and sectoral effects. For this purpose, the IMAGEM-Brumadinho model was developed, a Computable General Equilibrium (CGE) model specified for the economies affected by the disaster. The results indicate that the ITP was responsible for a significant increase in household consumption in the considered regions, which translates into economic growth or not depending on the inter-sectoral and regional trade relations of the municipalities. Overall, it is estimated that regions with a large increase in household consumption showed GDP growth, increased imports, and an increase in prices. Furthermore, transfers have a positive effect on services and trade.